2019
DOI: 10.1111/ecc.13095
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessments among patients with cancer: A scoping review

Abstract: Introduction Ecological momentary assessment (EMA) is an emerging method to assess an individual's current thoughts, affect, behaviour, physical states and contextual factors as they occur in real‐time and in their natural environment. Whereas EMA is frequently used in mental health, little is known about the added value of EMA in oncology research. This review aimed to synthesise methodological information and results of studies that applied EMA among patients with cancer to inform future researchers about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 32 publications
(221 reference statements)
1
52
0
Order By: Relevance
“…Implementation of a standardized method to screen for, and manage, the immediate needs of cancer patients at each cancer center is likely helpful for future management of crisis and pandemic situations. The use of electronic patient reported outcomes and further developments in ecological momentary assessment technologies will likely advance this agenda [6,7]. 2.…”
mentioning
confidence: 99%
“…Implementation of a standardized method to screen for, and manage, the immediate needs of cancer patients at each cancer center is likely helpful for future management of crisis and pandemic situations. The use of electronic patient reported outcomes and further developments in ecological momentary assessment technologies will likely advance this agenda [6,7]. 2.…”
mentioning
confidence: 99%
“…There is a large literature base focused on the ecological momentary assessment of symptoms such as pain, fatigue, and depression in real time. Although it is burdensome for patients relative to passive monitoring of behaviors, ecological momentary assessment can provide important information regarding daily and intraday variability in symptoms without recall bias 163 . For example, using real‐time, validated, smartphone‐based brain games Small et al 164 demonstrated significant intraday cognitive variability in patients with breast cancer.…”
Section: Digital Phenotyping: Mobile Technology To Collect Pghdmentioning
confidence: 99%
“…While causal relationships between strongly inter‐related variables may be advocated, the direction in the relationships among coping strategies and difficulties may not be ascertained by cross‐sectional analyses. Future research could employ time‐series designs in order to estimate dynamic networks in which an edge denotes a predictive relation (eg, higher avoidance predicting higher negative emotions) …”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Future research could employ time-series designs in order to estimate dynamic networks in which an edge denotes a predictive relation (eg, higher avoidance predicting higher negative emotions). 39…”
Section: Limitations and Strengthsmentioning
confidence: 99%